TET1 is a Tumor Suppressor That Inhibits Papillary Thyroid Carcinoma Cell Migration and Invasion. (8th February 2020) - Yu, Shuang; Yin, Yali; Hong, Shubin; Cao, Siting; Huang, Yanrui; Chen, Shuwei; Liu, Yujie; Guan, Hongyu; Zhang, Quan; Li, Yanbing; Xiao, Haipeng
Abstract : Background . Ten-eleven translocation (TET) enzymes catalyze the oxidation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) promoting demethylation in cells. However, the expression pattern and biologic significance of TET in papillary thyroid carcinoma (PTC) remain unclear. This study aimed to elucidate the biological functions of TET1 and the miRNA and mRNA expression levels in PTC cells with downregulated TET1. Methods . The expression of the TET family in 49 PTC tissues and corresponding tumor-adjacent tissues, as well as PTC cell lines (BCPAP, K1, and TPC-1) and the normal thyroid epithelial cell line (Nthy-ori 3-1), were detected using quantitative real-time polymerase chain reaction. The 5hmC level was detected in PTC tissues and cell lines using immunohistochemistry and dot blot assay, respectively. After silencing the TET1 gene with siRNAs in BCPAP and TPC-1 cells, cell proliferation was detected using EdU assay. Transwell assay was used to investigate cell migration and invasion. miRNA and mRNA expression arrays were conducted in TET1-depleted BCPAP cells. Results . The expression level of TET1 decreased in PTC tissues and cell lines and was consistent with the reduction in the 5hmC level. The knockdown of the TET1 gene promoted cell migration and invasion in BCPAP cells. The expression of miR-7, miR-15/16 cluster, and let-7 family was downregulated, while the expression of let-7e was upregulated after siRNA-TET1 treatment in BCPAP cells. The expression of WNT4, FZD4, CDK6, MCF2L, and EDN1 was upregulated as potential target genes of dysregulated miRNAs. Conclusion . The study showed that TET1 dysfunction inhibited the migration and invasion of BCPAP cells and might have a potential role in the pathogenesis of PTC.